Dynamic analysis of the tethered satellite system considering uncertain but bounded parameters - Xin Jiang; Zhengfeng Bai (Defence Technology)
Dynamic analysis of the tethered satellite system (TSS) can provide a fundamental guideline to the evaluation of performance and robust design of the system examined. Uncertainties inherited with the parameters would induce unexpected variation of the response and deteriorate the reliability of the system. In this work, the effect of uncertain mass of the satellites on the deployment and retrieval dynamics of the TSS is investigated. First the interval mode is employed to take the variation of mass of satellite into account in the processes of deployment and retrieval. Then, the Chebyshev interval method is used to obtain the lower and upper response bounds of the TSS. To achieve a smooth and reliable implementation of deployment and retrieval, the nonlinear programming based on the Gauss pseudo-spectral method is adopted to obtain optimal trajectory of tether velocity. Numerical results show that the uncertainties of mass of the satellites have a distinct influence on the response of tether tension in the processes of deployment and retrieval.